Enhancing Education Quality: The Transformative Role of ICT in Modern Teaching and Learning - Ragukumar Kannan; Jothye Akila; Elenna Elenche Zhia (Advances Educational Innovation, 2024)
Objective: This study examines the impact of information and communication technology (ICT) adoption on the quality of education, focusing on its influence on academic performance and student engagement in different educational institutions.Methods: Data were analysed using SPSS to explore the relationships between ICT adoption, academic performance and student engagement. A sample of 420 educational institutions in Thoothukudi, including primary, secondary and higher education levels, was selected using purposive sampling. Data were collected from institutional records, government education databases, and surveys of 35,000 students and 2,500 educators over the period 2019-2024. Regression analysis was used to assess the influence of ICT on student performance, with a focus on the effectiveness of ICT integration in modern teaching practices.Results: The results indicate a positive correlation between ICT integration and academic performance. Schools with advanced ICT tools showed higher student engagement, especially at the secondary and tertiary levels. However, challenges related to infrastructure and teacher preparedness were identified as barriers to effective ICT use.Novelty: This study provides new insights into how ICT adoption varies across educational levels and the specific challenges faced by different institutions, particularly in rural areas.Theoretical and policy implications: The findings emphasise the importance of improving ICT infrastructure and teacher training. Policy makers are encouraged to focus on equitable distribution of ICT and support for educators to improve learning outcomes through technology